Design Of Collection Sweetie Microsoft Access-Based Accounting Recording System - Meily Juliani; Jennica Jennica (ConCEPt - Conference on Community Engagement Project, 2023)
Collection Sweetie is a Micro, Small, and Medium Enterprise (MSME) that still use manual accounting transactions. This can cause time inefficiency in preparing financial report and information becomes inaccurate so that business owners don’t know the condition of their business well or to make good decisions. The design of an accounting system using Microsoft Access is carried out to assist MSME in overcoming the problem of using manual accounting records. The data collection method is carried out by observing and interviewing the owner of MSME. The output generated from designing an accounting system using Microsoft Access includes administrative bookkeeping and reports. The output of administrative bookkeeping includes a list of accounts, inventory, supplier, general journal, purchase journal, sales journal, and other journals. Output reports include inventory card, purchase report, sales report, financial position, income statement, and changes in equity. By designing an accounting system using Microsoft Access, it can make it easier for owners to record company transactions and become more efficient so that they can produce more accurate and reliable financial reports.